Standard Time Calculation Of Tempe Production Process Using Snapback Time Study Method (Case Study: Tn Group Home Industry) - et. al., Annisa Maharani Suyono, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In Indonesia, soybeans are consumed mostly in the form of traditional foods, tempe is not consumed as a raw food but in the form of cooked tempe and served as a delicacy or a side dish, often fried, boiled, steamed or roasted. The process of making tempe takes a long time compared to making tofu, so it becomes a problem that must be analyzed. Therefore, the researcher will calculate the process of making tempe to find out the standard time needed to make tempe. The research was carried out in one of the home industries in Bandung, Indonesia called the TN Group. At this time, the number of employees working at the TN Group is 18 people with 4 working hours per day. Every day the TN Group spends 1 quintal of soybeans to produce 150 packs of tempeh, each weighing 6 ounces of tempeh, selling for Rp. 6,000. with the production per day. 30 datas were collected using the snapback time study or repetitive timing method. By separating the types of work, we can calculate the cycle time, normal time, and standard time for each work process performed by workers by taking into account the adjustment factor and the allowance factor. From the calculation of the total standard time, the standard time for the new production process is 2 hours 44 minutes.